2018
DOI: 10.1080/1120009x.2018.1425279
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of tigecycline monotherapy versus combination therapy for the treatment of hospital-acquired pneumonia (HAP): a meta-analysis of cohort studies

Abstract: The broad spectrum antibiotic tigecycline shows promising efficacy against many multiple drug resistant (MDR) pathogens. However, its clinical efficacy in the treatment of hospital-acquired pneumonia (HAP) is unclear. Several studies have reported on the treatment failures of tigecycline monotherapy, suggesting that it may not be sufficient to control severe infections. Combination therapy has become an option to treat MDR bacterial infections. We conducted a literature search using PubMed, Cochrane Library, E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although we noticed that Food and Drugs Administration (FDA)-approved indications were only for cIAI, cSSSI, and CAP, not including HAP, due to ascended multidrug-resistant infections, TGC had been widely used for non-approved indications, among whom used in research related to CRAB HAP accounted for 1/3 [8]. A previous meta-analysis of 5 trials [19] analyzed the prognosis of patients with CRAB HAP receiving TGC monotherapy compared to those with TGC combination, no signi cant difference was from two prospective cohort studies (OR = 2.22, 95% CI 0.79-6.20, P = 0.13). Except for in-hospital mortality, Li Y et al [20] found that regimens containing TGC-CPS combination therapy patients with CRAB HAP were not superior to those with TGC monotherapy in clinical and microbiological e cacies.…”
Section: Discussionmentioning
confidence: 99%
“…Although we noticed that Food and Drugs Administration (FDA)-approved indications were only for cIAI, cSSSI, and CAP, not including HAP, due to ascended multidrug-resistant infections, TGC had been widely used for non-approved indications, among whom used in research related to CRAB HAP accounted for 1/3 [8]. A previous meta-analysis of 5 trials [19] analyzed the prognosis of patients with CRAB HAP receiving TGC monotherapy compared to those with TGC combination, no signi cant difference was from two prospective cohort studies (OR = 2.22, 95% CI 0.79-6.20, P = 0.13). Except for in-hospital mortality, Li Y et al [20] found that regimens containing TGC-CPS combination therapy patients with CRAB HAP were not superior to those with TGC monotherapy in clinical and microbiological e cacies.…”
Section: Discussionmentioning
confidence: 99%
“…32 Our previous meta-analysis results indicated that there was no significant association between high dose of TGC and mortality. 33 A review study showed that mortality with highdose tigecycline in the cohort studies ranged from 8.3% to 26%, while mortality in the low-dose groups (50 mg q12 h) ranged from 8% to 61% and depended on the underlying infection severity. Available data are limited regarding the effectiveness and safety of high-dose tigecycline.…”
Section: Discussionmentioning
confidence: 99%
“…The need for the use of multiple agents to effectively treat a disease would not be unique. Indeed, it has proved essential for the treatment of many forms of cancer [77,78], HIV/AIDS [79], and pneumonia [80].…”
Section: The Effects Of Cdnf and N4 In The Presence Of Mpp +mentioning
confidence: 99%